The Effect Of Professional Skepticism & Auditor's Independence On Detection Fraud - Inta Budi Setya Nusa (Institute of Computer Science (IOCS), 2021)
The growing economy is inseparable from the existence of fraud. For this reason, the services of an auditor are required to check whether the financial statements that have been prepared by the company are free from material misstatement and have been presented in accordance with generally accepted auditing standards, and have reflected the actual situation or manipulation of the financial statements was found. The purpose of this study was to determine how the influence of professional skepticism and independence on fraud detection. The research method used in this study is a descriptive and verification method with a quantitative approach. The population of this study is the external auditor of the Public Accounting Firm in Bandung with a sample of 38 respondents. Data were collected by distributing questionnaires. The data analysis technique used in this research is SEM-Partial Least Square (PLS) using SmartPLS 3.2.9 software. The results showed that professional skepticism and independence effect on fraud detection.